2015
DOI: 10.1007/s11626-015-9953-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNA-1 and microRNA-206 in the proliferation and differentiation of bovine skeletal muscle satellite cells

Abstract: MicroRNAs (miRNAs) have been found to play essential roles in muscle cell proliferation and differentiation. MicroRNA-1 (miR-1) and microRNA-206 (miR-206), which are similar and have the same seed sequence, have specific roles in modulating skeletal muscle proliferation and differentiation in vitro and in vivo. However, there is no information about their function during bovine skeletal muscle satellite cell development. In this study, the profiles of miR-1 and miR-206 and their biological functions in bovine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…In particular, class IIa HDACs (HDACs 4, 5, 7, and 9) plays an important role in the maintenance of muscle mass and protein degradation during muscle wasting . The reduced levels of HDAC4 promote myoblast differentiation, while increased levels of HDAC4 enhances skeletal muscle atrophy . Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, class IIa HDACs (HDACs 4, 5, 7, and 9) plays an important role in the maintenance of muscle mass and protein degradation during muscle wasting . The reduced levels of HDAC4 promote myoblast differentiation, while increased levels of HDAC4 enhances skeletal muscle atrophy . Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-206, which is located on chromosome 6 in a bicistronic cluster that belongs to a skeletal muscle-specific myomiR, is specifically expressed in muscles and it is believed to be an important regulator for myogenic differentiation [29,30]. As suggested by growing evidence, miR-206 has been linked with many human cancers including breast cancer, colon cancer, endometrial and endometrioid carcinoma, gastric cancer, lung cancer, glioma, laryngeal cancer, and rhabdomyosarcoma [3134].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dai et al (2016) demonstrated that miRNA-1 and miRNA-206 promote bovine skeletal muscle satellite cell myogenic differentiation and limit their proliferation by down-regulating PAX7 and HDAC4 expression. Through the use of deep sequencing technology, it has also been found that miRNA-2400, a bovine-specific miRNA, is involved in the differentiation of satellite cells and directly targets the 3′ untranslated regions of MYOG mRNA .…”
Section: Discussionmentioning
confidence: 99%
“…Most information on the satellite cells and their regulation and behavior during differentiation induction has been gained from studies using rodent animal models, whereas very limited information is available about satellite cells in large farm animals (Dai et al, 2016). Understanding the processes involved in the regulation of muscle differentiation is necessary to develop strategies for improving the efficiency of meat production.…”
Section: Introductionmentioning
confidence: 99%